2021
DOI: 10.1186/s12947-021-00248-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitral early-diastolic inflow peak velocity (E)-to-left atrial strain ratio as a novel index for predicting elevated left ventricular filling pressures in patients with preserved left ventricular ejection fraction

Abstract: Objectives We sought to explore the relationship between an index of left ventricular diastolic function parameters combined with left atrial strain and the diastolic function of patients with preserved ejection fraction. Methods We prospectively enrolled 388 patients with left ventricular ejection fraction (LVEF) ≥ 50%, 49 of whom underwent left heart catherization. Transthoracic echocardiography was performed within 12 h before or after the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In recent years, several studies have demonstrated an association between LASr and LVDD as well as increased LVFP in patients with coronary heart disease, heart failure, among others, and LA stiffness index are reliable parameters for identifying elevated LVEDP. 20,21 In this study, we applied these parameters to patients with AF and found that LASr, LA filling index, and LA stiffness index exhibited excellent accuracy in detecting elevated LAP, and non-inferior to the performance of conventional echocardiographic parameters commonly used for assessing LAP in AF patients. Furthermore, we pro-…”
Section: Discussionmentioning
confidence: 91%
“…In recent years, several studies have demonstrated an association between LASr and LVDD as well as increased LVFP in patients with coronary heart disease, heart failure, among others, and LA stiffness index are reliable parameters for identifying elevated LVEDP. 20,21 In this study, we applied these parameters to patients with AF and found that LASr, LA filling index, and LA stiffness index exhibited excellent accuracy in detecting elevated LAP, and non-inferior to the performance of conventional echocardiographic parameters commonly used for assessing LAP in AF patients. Furthermore, we pro-…”
Section: Discussionmentioning
confidence: 91%
“…LA reservoir strain (LASr) has been demonstrated to be a surrogate marker for LV filling pressure. In patients with elevated LV end diastolic pressure (measured by invasive catheterization), LASr was significantly reduced (sensitivity 74.2%, specificity 94.4%) 133 . Furthermore a reduction in LASr has been associated with increased pulmonary vascular resistance and reduced peak oxygen consumption.…”
Section: Cardiac Remodelling With Angiotensin Receptor Neprilysin Inh...mentioning
confidence: 98%
“…In patients with elevated LV end diastolic pressure (measured by invasive catheterization), LASr was significantly reduced (sensitivity 74.2%, specificity 94.4%). 133 Furthermore a reduction in LASr has been associated with increased pulmonary vascular resistance and reduced peak oxygen consumption. In HFpEF, LASr was most strongly correlated with adverse events, and independently associated with cardiovascular hospitalizations or death when compared with LV, RV, and LA strain.…”
Section: Cardiac Remodelling With Angiotensin Receptor Neprilysin Inh...mentioning
confidence: 99%
“… 5 Several studies have shown that left atrial strain is negatively correlated well with LVFP or PCWP. 6 , 7 , 8 , 9 However, diastolic dysfunction per se is not tantamount to HFpEF.…”
Section: Introductionmentioning
confidence: 99%